Base de dados de informações jornalísticas sobre a Amazônia: ciência, tecnologia e meio ambiente – BDIJAm: em busca da qualidade - RODRIGUES, Anderson Luis Cardoso (2011)
This paper presents the evaluation of quality of the Database of Press Information about Amazon: Science, Technology and Environment (Brazilian acronym: BIDJAm). This study is part of the project “Amazonian Themes: Annotated Reports and Information Quality about Science, Technology and Environment”, proposed by Museu Paraense Emílio Goeldi. Such data was obtained by the application of a questionnaire submitted to its users aiming at identifying positive aspects and possible gaps in the service. Main results pointed to the relevance of themes in the database as well as to the need of developing actions in order to improve the structure for information recovery. In conclusion, this present study realized that all database must be continuously improved as for BDIJam users consider it of great relevance to society as a tool of preservation of Amazon´s social memory.